2015
DOI: 10.1016/j.ijgo.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Results of screening for cervical cancer among pregnant and non‐pregnant women in Brazil

Abstract: Mandatory cervical cytology screening does not seem to be necessary for pregnant women; protocols in place for non-pregnant women should be followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…One might argue that therefore the pregnant women group might contain more early lesions with potentially benign biologically behavior. On the other hand, a recent study compared screening results in pregnant and non-pregnant women and could not detect any difference between CIN incidence [ 35 ]. Follow-up algorithms slightly differed between pregnant and non-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…One might argue that therefore the pregnant women group might contain more early lesions with potentially benign biologically behavior. On the other hand, a recent study compared screening results in pregnant and non-pregnant women and could not detect any difference between CIN incidence [ 35 ]. Follow-up algorithms slightly differed between pregnant and non-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some alterations in sexual behavior over the last years, 1 changes in screening programs have postponed the age of the first screening tests, 1 5 and the influence of age at first sexual intercourse as a risk factor is in discussion. 7 15 16 19 20 After that, the amount of cancers at age 25 has increased dramatically; however, these cases are micro-invasive, with excellent prognosis 5 6 and rare deaths. 7 Therefore, there is doubt if screening women aged 20–24 years can impact the incidence of cancer in those under 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In addition, the treatment for precursor lesions in this age group is related to an increased risk of premature labor due to the anatomical damage that occurs during the procedure. 1,8 It has been suggested that early sexual intercourse can be a risk factor for cervical cancer in young women, 1,14,15 since it is a risk factor for HPV infection. 16 On the other hand, screening patients under the recommended age may impact the efficiency of a program through the improper use of the logistic and human resource structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation